Involvement of NO in Antinociception of NSAIDS in Murine Formalin Hind Paw Assay - Noriega, Viviana; Miranda, Hugo F.; Prieto, Juan Carlos; Sotomayor-Zárate, Ramón; Sierralta, Fernando (Drug Research, 2020)
There are different animal models to evaluate pain among them the formalin hind paw assay which is widely used since some of its events appear to be similar to the clinical pain of humans. The assay in which a dilute solution of formalin is injected into the dorsal hindpaw of a murine produces two ‘phases’ of pain behavior separated by a inactive period. The early phase (Phase I) is probably due to direct activation of nociceptors and the second phase (Phase II) is due to ongoing inflammatory input and central sensitization. Mice were used to determine the potency antinociceptive of piroxicam (1,3,10,and 30 mg/kg), parecoxib (0.3, 1,3,10 and 30 mg/kg), dexketoprofen (3,10,30 and 100 mg/kg) and ketoprofen (3,10,30 and 100 mg/kg). Dose-response for each NSAIDs were created before and after 5 mg/kg of L-NAME i.p. or 5 mg/kg i.p. of 7-nitroindazole. A least-squares linear regression analysis of the log dose–response curves allowed the calculation of the dose that produced 50% of antinociception (ED50) for each drug. The ED50 demonstrated the following rank order of potency, in the phase I: piroxicam > dexketoprofen > ketoprofen > parecoxib and in the phase II: piroxicam > ketoprofen > parecoxib > dexketoprofen. Pretreatment of the mice with L-NAME or 7-nitroindazol induced a significant increase of the analgesic power of the NSAIDs, with a significant reduction of the ED50. It is suggested that NO may be involved in both phases of the trial, which means that nitric oxide regulates the bioactivity of NSAIDs.
Keywords: anti-inflammatory drugs; pharmacology; inflammation